Peningkatan Pengetahuan Kader Posyandu melalui Aplikasi MAGENTA (Monitoring Status Gizi dan Edukasi Anak Balita) - Yuliana, Indah; Ramadhani, Ira Dewi; Harwanto, Fatria; Aerosta, Danny Kusuma (Universitas Pahlawan Tuanku Tambusai, 2024)
The role of cadres in Posyandu activities is vital to detect growth and development problems in children under five in their environment. Technology that is developing over time makes it possible for several health services including recording the results of posyandu activities which are made in the form of an Android-based application. The aim of this study was to analyze differences in knowledge before and after being given the MAGENTA application training intervention. This research was conducted in October 2023 at the Kenten Palembang Community Health Center involving 34 posyandu cadres. Data analysis was carried out on the results of the trial evaluation which began with a normality test, and continued with a difference test on the results of the pre-test and post-test assessments. The MAGENTA application is an alternative form of guidance for posyandu cadres in monitoring child growth and providing nutrition education to mothers of toddlers during posyandu activities. The results of the analysis show that there is a significant difference in knowledge between before and after training in using the MAGENTA application regarding calculating and inferring nutritional status, and health promotion regarding attitudes towards the nutritional status of toddlers. There was a significant increase in cadre knowledge before and after the training.